Multivariate optimisation of a novel green microextraction method for Fe (III) determination in environmental samples by FAAS - YILDIZ, NİLGÜN; AYDIN URUCU, OYA (TAYLOR & FRANCIS LTD, 2022)
Industrial development has led to increased heavy metal pollution in bodies of water all over the world. Numerous methods are being developed with the aim of detecting and subsequently removing heavy metal ions from water with hopes of reversing pollution. Here, we present a novel and ecological switchable solvent-based liquid phase microextraction (SS-LPME) method that detects Fe (III) in water samples before they can be tested on flame atomic adsorption spectrometry. In this method, 2-(5-Bromo-2-pyridylazo)-5-(diethylamino) phenol was selected as a complexing agent and switchable polarity solvent was formulated with N, N-dimethyl-n-octylamine. Box-Behnken response surface design was used to investigate and optimise factors associated with the extraction recovery. When the optimal conditions were reached, a linear calibration curve was achieved at 0.05-400 mu g L-1. The preconcentration factor was 200, the detection limit was 0.015 mu g L(-1)with the relative standard deviation (RSD) of 2.2% (at 30 mu g L-1; n = 8). Water samples and wastewater reference material (SPSWW1) were used to test the applicability and success of the method.
Keywords: Separation; preconcentration; iron; Box-Behnken; response surface design; LIQUID-PHASE MICROEXTRACTION; CLOUD POINT EXTRACTION; ADSORPTION-KINETICS; AQUEOUS-SOLUTION; TRACE-LEVEL; METAL-IONS; PRECONCENTRATION; SEPARATION; WATER; IRON(III)